Application of Surgical Safety Checklist (WHO) at Al- Diwaneyah Teaching Hospital - Ali Jawad Hamza Al-Shammari (Journal of Global Pharma Technology, 2020)
Background: Surgery have been considered as one of the global health care important part, however the surgical complications are still common, but can be prevented. Till now, surgery is an essential component of public health and its role is increasing rapidly. Aims: Present study aims to use a safety checklist items to improve team surgical care which will reduce complications and deaths associated with surgery. Patient and Methods: This prospective study enrolled 162 patients using checklist of surgical safety consist of 19 items with different types of operations at Al-Diwaneyah Teaching Hospital in Iraq during the period 1st of February 2018 until 1st of February 2019. We follow the patients until 30 days after surgical intervention. Results: After applying the 19 items of surgical safety checklist to 162 patients, the risk of the surgical site infection(SSI), respiratory complications, missed gauze and risk of blood loss (3.7%, 2.4%, 0.6% and 1.85%) respectively were comparable to the results of the World Health Organization. Pulse oximeter was used in 92.5% and site marking in 65.4%. In 61.73% of patients received antibiotic prophylaxis in which just 3.7% developed surgical site infection, while the extended regime in 38.27%, there is 9.8% with SSI. No mortality reported during the collection of the data. Conclusions: The surgical checklist is a simple and effective method in reducing surgical complications. WHO recommends use of the checklist in all surgical operations and encourages clinicians to modify the list for different specialty and hospitals. Keywords: Safety check list, Surgical site infection, Surgical complications, Basic surgical care.